Evaluating the efficacy, safety, and immunogenicity of FDA-approved RSV vaccines: a systematic review of Arexvy, Abrysvo, and mResvia - Alandijany, Thamir A.; Qashqari, Fadi S. (Frontiers in Immunology, 2025)
BackgroundRespiratory Syncytial Virus (RSV) poses a major health threat to older adults, pregnant women, and high-risk populations. We systematically evaluated the efficacy, immunogenicity, and safety of three FDA-approved RSV vaccines: Arexvy, Abrysvo, and mResvia.MethodsFollowing PRISMA 2020 guidelines, we searched PubMed, ClinicalTrials.gov, FDA, and Vaccine Adverse Event Reporting System (VAERS) up to March 2025. Of 1,250 identified records, 24 studies (14 RCTs, 7 observational, 3 post-marketing) met inclusion criteria. Risk of bias was assessed using the Cochrane RoB tool and Newcastle–Ottawa Scale. PROSPERO registration: CRD420250651132.ResultsIncluded studies enrolled over 50,000 participants across North America, Europe, Asia, and Latin America. Arexvy reduced RSV-related hospitalizations in older adults by 60–65% (95% CI: 56–66%); Abrysvo showed 58–63% efficacy in older adults and 68–72% protection against infant RSV hospitalization via maternal immunization. mResvia demonstrated 55–58% efficacy against RSV illness. All vaccines induced 5–7-fold increases in neutralizing antibody titers, with responses sustained for up to 12 months. Safety profiles were favorable: local injection site pain occurred in ~23–29%, systemic symptoms in 7–11%, and serious adverse events in <1%. No new safety concerns were identified in post-marketing surveillance.ConclusionFDA-approved RSV vaccines provide robust protection against RSV in high-risk populations, with sustained immunogenicity and acceptable safety. While findings are promising, generalizability to underserved regions remains limited, and long-term effectiveness data are still emerging. Continued real-world monitoring and head-to-head comparisons are needed to inform global immunization strategies.Clinical Trial Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/, identifier CRD420250651132.